Entanglement of Hair Iodine and Selenium Nutritional Status. (29th May 2020) - Momčilović, Berislav; Mimica, Ninoslav; Prejac, Juraj
Abstract: Objectives: Iodine and selenium are two essential trace elements intimately associated with the thyroid gland function. The aim of this study was to assess the combined hair iodine and selenium frequency distribution in the hair to assess their nutritional status and their mutual ratio. Methods: Hair was collected in 1073 healthy adult subjects (339 men and 729 women) living in Zagreb, CROATIA. Hair samples were analyzed for Se and I by the ICP-MS at the CBM, Moscow, RUSSIA, an internationally ISO certified analytical laboratory. I and Se were detected in all the 1073 hair samples. The frequency distribution of hair I and Se was statisticaly analyzed with the median derivative bioassay method of the log transformed data. Results: The adequate nutritional status of iodine and selenium in the hair is shown by the linear response interval on ther sigmoid curves. The adequate nutritional status was associated with the hair iodine and selenium (µg·g −1 ) of men (M) and women (W), respectively. Iodine was M 0.506 W 9.482, and selenium M 0.346 and W 0.269, Over the same linear (adequate) interval of the responsive sigmoid curve of the combined iodine and selenium dietary intake (I&Se) the adequate dietary interval was (µg·g −1 ) 0.209–2.433 (r 2 0.90); their combined ratio was also constant at (log µg·g −1 ) 0.740 within the ±2% difference between men and women. Conclusions: Iodine and selenium deposition into the hair are closely entangled over the adequate interval of their dietary intake. The iodine to selenium mutual ratio should be also kept constant to provide the most optimal nutrition environment for the thyroid gland function. Single element supplementation should be always viewed on how it may affect the rest of the elements in our body. Funding Sources: Institute for Research and Development of Sustainable Eco Systems, 10, 000 Zagreb, Croatia.